Hyperbole in Indonesian Song Lyrics - I Dewa Putu Wijana (Universitas Sanata Dharma, 2025)
Language is pivotal in fulfilling human communicative needs, such as transactional and interactional functions. In the latter function, language is employed, one of which is to build social and personal attitudes, or so-called poetic or imaginative function. Such functions can be accessed through songs or song lyrics. Motivated by the previous argument, this paper aims to describe construction types and categories of hyperbolic expressions found in various Indonesian song lyrics, comprising the genres of “kroncong,” “dangdut,” and other popular songs. To provide the evidence, this study collected data from YouTube and carefully examined how the song lyrics involve hyperbolic expressions. The analysis also comprised identifying the types of hyperbolic expressions in terms of their linguistic constructions. Analysis reveals that hyperbole is constructed in either positive or negative sentences, metaphors, superlative, and serial adjectival constructions. Those hyperbolic expressions can at least be classified into five categories, i.e. quantity hyperbole, quality hyperbole, distance hyperbole, time hyperbole, space hyperbole, and action hyperbole. These categories seem to closely relate to the scope of human perceptions about everything they find in the world. They will always have associations with number, state, distance, time, space, and actions anyone can perform. This study concludes the intertwined relationship between language and human behaviors.